AN ANALYSIS OF ASPECTS OF THE PROPOSED REFORM OF THE FINANCIAL CONSUMER COMPLAINT RESOLUTION MECHANISMS IN THE SOUTH AFRICAN BANKING SECTOR - Michel M Koekemoer (Obiter, 2021)
One objective of the revised South African market conduct regulatory framework for the financial sector is to introduce an effective dispute resolution framework. The Financial Sector Regulation Act, and the Act to follow the Draft Conduct of Financial Institutions Bill, potentially address some of the deficiencies associated with the old dispute resolution framework. This article makes a distinction between the old and new regulatory provisions concerning internal dispute resolution and external dispute resolution structures in the banking sector. This research highlights the changes involved in the new regulatory framework and identifies which aspects of the amended regulatory framework aim to address a particular issue associated with the old dispute resolution framework. It is not argued whether this legislation will achieve the fair treatment and protection of financial customers in the banking sector, as only time will tell. However, it is acknowledged that the new structure will improve consistency and efficacy in this dispute resolution structure.